Dendroclimatic response of Pinus tabuliformis Carr. along an altitudinal gradient in the warm temperate region of China - Ning, Peng; Zhang, Min; Bai, Tianyu; Zhang, Bin; Yang, Liu; Dang, Shangni; Yang, Xiaohu; Gao, Runmei (Frontiers in Plant Science, 2023)
Global warming climate changes the sensitivity of tree radial growth response to climate factors along the altitudinal gradient. In this work, we took Pinus tabuliformis Carr. of Zhongtiao Mountains in Shanxi Province, China. as objects, tree-ring width chronologies of this species at three altitude gradients, 1200-1300m (low altitudes, L), 1300-1400m (medium altitudes, M) and 1400-1500m (high altitudes, H), respectively were studied, aimed to reveal the trend of radial growth of P. tabuliformis under the background of the global warming. The results showed that: (1) From 1958 to 2017, study area showed a warming and drying climate, with 1958–1996 as a stable period and 1997–2017 as a rapid change period; (2) In stable period, the radial growth of P. tabuliformis at low altitude showed significantly negative response to the high temperature and positive response to the rainfall in May and June. While the high altitude ones were mainly positively correlated with the monthly mean maximum temperature in August and precipitation in May. When in the rapid change period, the radial growth of P. tabuliformis was influenced by the rapid increase of temperature. Low-altitude trees were positively influenced by the monthly mean minimum temperature in January and the monthly maximum temperature in April, whereas high-altitude ones positively responded to the low temperature in February; (3) With the increase of altitude, tree radial growth was more influenced by temperature than by precipitation, which was shown that the contribution rate of temperature factor increased from 67.24% of low altitude to 79.33% of high altitude in 1958-1996, and from 65.79% of low altitude to 100% of high altitude in 1997-2017; (4) The response of tree radial growth to climate change at different altitudes are inconsistent. Radial growth of low- and medium-altitude trees benefited from the increase of temperature. Drought stress caused by temperature rise at high altitudes inhibited the tree radial growth, and did not show the upward movement of tree lines caused by temperature rise either. The outcome would be of great significance for understanding the impact of climate change on tree growth adaptation, succession and sustainable management of forest ecosystems in Zhongtiao Mountains.